PENDAMPINGAN PENYUSUNAN MENU GIZI SEIMBANG DI POSYANDU KHUSUS SAD DI DESA DWI KARYA BAKTI KECAMATAN PELEPAT KABUPATEN BUNGO TAHUN 2023 - Kalsum, Ummi; Rahmad, Rizki Ibnu; Adriani, Adriani; Ridwan, M.; Halim, Rd.; Sitanggang, Hendra Dhermawan; Suryani Nasution, Helmi; Noerjoedianto, Dwi (Prodi Ilmu Kesehatan Masyarakat, FKIK Universitas Jambi, 2023)
The Anak Dalam Tribe (SAD) is a remote traditional community in Jambi Province, spread across several districts, sub-districts and villages, one of which is at Dwi Karya Bhakti Village, Bungo Regency. Health is still a problem in the SAD community, especially nutritional problems such as stunting, malnutrition and anemia. Posyandu is an effective effort to improve community-based health. However, the SAD community needs assistance, through Posyandu which is specifically designed and adapted to the basic capabilities and limited conditions of this community. The aim of the activity was to provide educational assistance in preparing a balanced nutritional menu for the SAD community in Dwi Karya Bhakti Village, Bungo Regency. This activity was carried out through comprehensive assistance from the Matching Fund Program SAD CARE For Health Team and by placing 5 students to live in the SAD community with partners for 6 months (July to December 2023). The activity was carried out in several steps, namely approaching traditional leaders, interpersonal assistance for SAD Special Posyandu cadres, nutrition education, and monitoring the growth and development of toddlers and pregnant women. Posyandu cadres are provided with local language educational media prepared by the Team. This educational assistance activity for cadres at the special posyandu for SAD has been carried out well. There has been an increase in knowledge about nutrition and how to prepare a balanced nutritional menu by Posyandu cadres specifically for SAD and also the SAD community, especially mothers of toddlers who come to Posyandu. It is hoped that this activity can contribute to improving the public health of the Anak Dalam Tribe community in Dwi Karya Bhakti Village, Pelepat District, Bungo Regency, resulting in an increase in the nutritional status of toddlers and other family members